Yield and nutritional quality of sweet lupine (Lupinus angustifolius) grown in Midaltitudes of Lemo District, Hadiya Zone, Southern Ethiopia - Tessema, Fikadu; Shawel, K.; Bezabih, Melkamu (Hindawi Limited, 2021)
The study was conducted to determine the yield and nutritional quality of sweet lupine (Lupinus angustifolius.) grown in midaltitude of Lemo District, Southern Ethiopia. The yield and nutritive value of sweet lupine in terms of quantity and quality was conducted using a factorial experiment arranged in a randomized complete block design (RCBD) with three replications. The treatments for the study were two sweet lupine varieties (Vitabore and Sanabore), two locations (Upper Gana and Jewe Kebeles, and six levels of planting spacing: 30 cm × 7 cm (S1), 40 cm × 7 cm (S2), 30 cm × 15 cm (S3), 40 cm × 15 cm (S4), 30 cm × 20 cm (S5), and 40 cm × 20 cm (S6)). The yield, chemical composition, and digestibility among parameters were studied. Sweet lupine varieties in Upper Gana Kebele gave the highest green forage yield (39.58 t/ha) and forage dry matter (4.84 t/ha) at 30 cm × 7 cm planting spacing, respectively. Seed yield (SYD) (t/ha) was highly affected ( P < 0.01 ) by location. The maximum seed (2.98 t/ha) yield was observed in Upper Gana Kebele with the minimum (2.15 t/ha) at Jewe Kebele. The forage in Jewe Kebele gave the highest organic matter (OM) (87.01%) and acid detergent fiber (ADF) (37.50%) content at a stage of 100% flowering. Sweet lupine forage in Upper Gana Kebele gave the highest crude protein (CP) content (23.11%) while the highest forage CP content was recorded at a planting space of 40 cm × 20 cm (23.67%). Sweet lupine forage gave the maximum in vitro organic matter digestibility (IVOMD) (69.10%) at a spacing of 40 cm × 20 cm in Upper Gana. The highest CP (29.11%) content and IVOMD (80.49%) of seed were recorded in Upper Gana Kebele. The overall result of this study suggested that green forage yield and forage dry matter yield are affected by location, planting spacing, and stage of flowering, whereas the chemical composition of sweet lupine forage was affected by location and variety interaction (dry matter and acid detergent fiber), location and stage of flowering interaction (OM, ADF and total ash), location (CP, metabolizable energy (ME), and IVOMD), planting spacing (CP and IVOMD), and stage of flowering (CP and ME). On the other hand, sweet lupine seed yield, seed CP, and IVOMD were affected by location. The large differences in yield and nutritive values observed among sweet lupine varieties, growth environment, planting spacing, and their interactions entail consideration of these factors for appropriate utilization of sweet lupine as a feed resource for livestock.